The Impact of Work Environment and Organizational Commitment on Employee Retention at PT. Putra Tani Bhinneka - Aan Fakhrur Rofiudin; Khotim Fadhli (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Human Resource Management plays a strategic role in ensuring employee retention, particularly in the face of global competition. This study examines the influence of the work environment and organizational commitment on employee retention at PT. Putra Tani Bhineka. A quantitative approach with a cross-sectional design was employed, utilizing a sample of 40 employees selected through saturated sampling. Data were collected through questionnaires, supported by interviews, and analyzed using multiple linear regression. The results show that both the work environment and organizational commitment have a simultaneous positive effect on employee retention, accounting for 28.2% of the variation. These findings emphasize the importance of creating a supportive work environment and enhancing organizational commitment to retain skilled employees. The study provides practical recommendations for the development of effective employee retention strategies that contribute to long-term business sustainability. Keywords: work environment; organizational commitment; employee retention; human resource management; PT. Putra Tani Bhineka.